Gender Patterns of Eldercare in China. Issue 2 (3rd April 2018) - Chen, Xinxin; Giles, John; Wang, Yafeng; Zhao, Yaohui
ABSTRACT: Using the baseline wave of the China Health and Retirement Longitudinal Study (CHARLS), collected from 2011 to 2012, this study finds that among those age 60 and above, women are 7.6 percent more likely than men to have care needs and 29.3 percent more likely than men to have unmet needs; and that most of the gender gap in unmet needs is explained by the existence and health status of a spouse. Further analysis reveals a sharp gender division in patterns of family care in China. While men are more likely to receive care from their wives, women are primarily cared for by their children. Marital status and spouse health also affect provision of care, with infirm women who have healthy husbands less likely to receive care than infirm men with healthy wives. The findings have important implications for designing gender-sensitive policies in eldercare.